2020
DOI: 10.15252/embj.2020104820
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into mammalian mitochondrial translation elongation catalyzed by mt EFG 1

Abstract: Mitochondria are eukaryotic organelles of bacterial origin where respiration takes place to produce cellular chemical energy. These reactions are catalyzed by the respiratory chain complexes located in the inner mitochondrial membrane. Notably, key components of the respiratory chain complexes are encoded on the mitochondrial chromosome and their expression relies on a dedicated mitochondrial translation machinery. Defects in the mitochondrial gene expression machinery lead to a variety of diseases in humans m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 103 publications
(180 reference statements)
6
60
2
Order By: Relevance
“…Superimposition of our Class I complex with the RRFmt-unbound human (Amunts et al, 2015), bovine (Sharma et al, 2003) and porcine (Greber et al, 2015) 55S mitoribosomes showed that the small 28S subunit was rotated counter-clockwise by about 8.5° with respect to the large 39S subunit (Fig. S3B), similar to the "ratchet-like inter-subunit rotation" observed in the bacterial 70S ribosome Agrawal, 2000, 2001) and the 55S mitoribosomes complexed with translational factors (Koripella et al, 2020;Koripella et al, 2019b;Kummer and Ban, 2020;Kummer et al, 2018). In addition to the inter-subunit rotation, the head domain of the 28S subunit is rotated by about 4° towards the tRNA exit (E) site in a direction roughly orthogonal to the inter-subunit motion (Fig.…”
Section: Rrfmt Binding Stabilizes the Rotated State Of The 28s Subunisupporting
confidence: 71%
See 1 more Smart Citation
“…Superimposition of our Class I complex with the RRFmt-unbound human (Amunts et al, 2015), bovine (Sharma et al, 2003) and porcine (Greber et al, 2015) 55S mitoribosomes showed that the small 28S subunit was rotated counter-clockwise by about 8.5° with respect to the large 39S subunit (Fig. S3B), similar to the "ratchet-like inter-subunit rotation" observed in the bacterial 70S ribosome Agrawal, 2000, 2001) and the 55S mitoribosomes complexed with translational factors (Koripella et al, 2020;Koripella et al, 2019b;Kummer and Ban, 2020;Kummer et al, 2018). In addition to the inter-subunit rotation, the head domain of the 28S subunit is rotated by about 4° towards the tRNA exit (E) site in a direction roughly orthogonal to the inter-subunit motion (Fig.…”
Section: Rrfmt Binding Stabilizes the Rotated State Of The 28s Subunisupporting
confidence: 71%
“…EF-G2mt has about 36 % aa sequence identity to EF-G1mt and about 30 % aa identity to both its bacterial homologues. Some mammalian mitochondrial translation steps are now better understood through determination of the cryo-EM structures of the initiation (Koripella et al, 2019a;Kummer et al, 2018;Yassin et al, 2011) and the elongation (Koripella et al, 2020;Kummer and Ban, 2020) complexes at highresolution. Our previous study of the human mitoribosome recycling complex of the RRFmtbound 55S (Koripella et al, 2019b) provided useful insights into the mito-specific aspects of the recycling process, but a complete 55S mitoribosomal recycling complex comprising both RRFmt and EF-Gmt remained elusive.…”
Section: Introductionmentioning
confidence: 99%
“…This structural rearrangement during mtSSU rotation suggests a coordinated movement of the mtSSU rotation and mL108 to the L1 stalk. The involvement of mitochondria-specific elements in coordination of tRNA movement has been recently reported also in other systems 2022 .…”
Section: Resultsmentioning
confidence: 67%
“…coordinated movement of the mtSSU rotation and mL108 to the L1 stalk. The involvement of mitochondria-specific elements in coordination of tRNA movement has been recently reported also in other systems [21][22][23] .…”
Section: Resultsmentioning
confidence: 67%